Réponses

2013-07-31T13:31:38+02:00

A  =  36 − 25x²

    =  6² − (5x)²

    =  (6 + 5x) 6 − 5x)

 

 

B  =  100 + 60x + 9x²

     =  10² + 2(10)(3x) + (3x)²

     =  (10 + 3x)²

 

 

C  =  2i (i+1) + 2i (2+i)

     =  2i (i + 1 + 2 + i)

     =  2i (2i + 3)

 

 

D  =  b² − 10b + 25

     =  (b)² − 2(b)(5) + (5)²

     =  (b − 5)²

 

 

E  =  (2 − x)² + (2 − x) (9 + x)

     =  (2− x) (2 − x) + (2 − x) (9 + x)

     =  (2 − x) (2 − x + 9 + x)

     =  (2 − x) (11)

     

 

F  =  (5x + 1)² − 81

    =  (5x + 1)² − 9²

    =  (5x + 1 + 9) (5x + 1 − 9)

    =  (5x + 10) (5x − 8)

 

 

G  =  (7d + 2)² − (3d + 4)²

     =  [ (7d + 2) + (3d + 4) ] [ (7d + 2) − (3d + 4) ]

     =  (10d + 6) (4d − 2)